(untitled) (The Spectrum, 2023)
Broadly, this article provides a three-fold synoptic sketch of rhetoric. A survey of the historical development of rhetoric that stretches as far back as the fifth century BC in Greece dominates the first part. The major issue, here, highlights the challenges and ambiguities that attend the attempt in defining the term rhetoric. Leading on from this historical survey, the second part casts light on how rhetorical practices advanced beyond the pale of Greek tradition. At the center of this part is a general description of the way rhetoric was practiced and applied in a diverse domain of academic disciplines. The last part focuses on the awareness that rhetoric should be reconstructed and theorized in a new light. Designed on qualitative methodology, especially as an attempt of library research, this paper draws on secondary sources. In addition to providing a general acquaintance, this article tries to carve out the changes that the scholarship of rhetoric has undergone, which might benefit the nascent researchers pursuing rhetorical scholarship in future.